PENINGKATAN HASIL BELAJAR MATERI FUNGSI KOMPOSISI DAN INVERS BERBANTUAN YOUTUBE DI MASA TATAP MUKA TERBATAS - Mellawaty Mellawaty; Tamurih Tamurih; Zuhrotul Mufidah (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2022)
This study aims to determine whether learning assisted by YouTube learning videos can improve student learning outcomes in the material of composition functions and inverse functions. This research is a Classroom Action Research conducted at Madrasah Aliyah Negeri 1 Indramayu. The subjects in this study were students of class X MIPA 1, totaling 23 students. The instrument used in this research is a formative test given every cycle to measure the increase in student learning outcomes in mathematics. The data processing learning outcomes obtained an average of 49.02 in the first and76.82 in the second. Likewise, from the increase in the number of students who achieve mastery learning, namely from the first cycle, as many as 5 of 23 students or 21% with shallow completeness criteria, in the second cycle, 20 of 23 students or 91% withvery high completeness criteria. Based on these results, it can be said that the learning outcomes of the composition function and inverse function material can be increased with the help of learning videos from youtube.